The Review of Learner’s Autonomy towards Learning English as a Foreign Language among College Students in China - Zhang, Hui (Technium Social Sciences Journal, 2021)
Learner’s autonomy has changed many aspects of society. At the same time Learner’s autonomy has become one of the most popular issues in education, especially in language learning. A large number of countries come to realize the importance of the learner’s autonomy in colleges and the significance of mastering the knowledge and basic skills of it in education. China is no exception. Since China has a considerable amount of English learners, more and more teachers, experts and organizations begin to pay attention to learner’s autonomy in the language teaching and learning process, which has been regarded as some kind of improvement and reform in the field of education. Therefore, research on learner’s autonomy towards learning English as a foreign language among college students in China is very important. This paper is divided into seven parts: the first part is the background of College English learner’s autonomy in China; the second part explains the main factors influencing the learner’s autonomy; the third part describes the different approaches to increase learner’s autonomy; the fourth part focuses on the current problems in learner’s autonomy; the fifth part is about solutions to solve the problems; the next part states the application of learner’s autonomy; the last part is the conclusion. All in all, this paper attempts to contribute to the growing understanding of learner’s autonomy, especially towards English teaching and learning among college students in China, which will be extremely beneficial for the improvement of quality of English education, and hopefully offer some references for the future researches in this area.